2022
DOI: 10.1186/s40168-021-01205-8
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota–derived metabolite 3-idoleacetic acid together with LPS induces IL-35+ B cell generation

Abstract: Background IL-35–producing Bregs and Treg cells critically regulate chronic illnesses worldwide via mechanisms related to disrupting the gut microbiota composition. However, whether the gut microbiota regulates these IL-35+ cells remains elusive. We herein investigated the regulatory effects of the gut microbiota on IL-35+ cells by using genetically modified mouse models of obesity. Results We first found that gut Reg4 promoted resistance to high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 75 publications
(103 reference statements)
1
22
0
Order By: Relevance
“…CD19 + IgM + IgD + IL10 + CD1d high CD5 low CD11b low CD21/CD35 Low CD23 Low CD25 Low CD72 low CD69 − CD138 low/− CD40 low/− CD86 low/− cells [ 112 ], which are different from IgG-producing Bregs but similar to IgM + IgD + Bregs [ 110 ]. These Bregs restrain excessive inflammatory responses [ 113 ] and contribute to the maintenance of immunological tolerance [ 114 ].…”
Section: Regulation Of Trp Metabolites From Gut Microbiota In the Imm...mentioning
confidence: 99%
See 1 more Smart Citation
“…CD19 + IgM + IgD + IL10 + CD1d high CD5 low CD11b low CD21/CD35 Low CD23 Low CD25 Low CD72 low CD69 − CD138 low/− CD40 low/− CD86 low/− cells [ 112 ], which are different from IgG-producing Bregs but similar to IgM + IgD + Bregs [ 110 ]. These Bregs restrain excessive inflammatory responses [ 113 ] and contribute to the maintenance of immunological tolerance [ 114 ].…”
Section: Regulation Of Trp Metabolites From Gut Microbiota In the Imm...mentioning
confidence: 99%
“…The relationship between IL-35 and NFκB has been reported. IAA by the gut microbiota, together with LPS, can activate NF-κB through TLR4 to induce the generation of IL-35 + cells [ 112 ]. IAA with LPS promotes the activity of transcription factors PXR, RXR and CAR, which are necessary for the expression of IL-35 [ 112 ].…”
Section: Regulation Of Trp Metabolites From Gut Microbiota In the Imm...mentioning
confidence: 99%
“…The abundance of Akkermansia, Blautia, and Bifidobacterium was positively correlated with tryptophan levels, indicating that there were more probiotics and more tryptophan in the MFE group to activate AhR. A previous study suggested that tryptophan metabolites of the gut microbiota suppress liver inflammation [7], and the 3-indoleacetic acid produced by the intestinal flora helps mice lose weight [45].…”
Section: Discussionmentioning
confidence: 91%
“…Still, no research on Bacteroides, indole synthesis, and IL-22 secretion has been conducted, so further studies are needed to verify the possibility that IAA produced by other Bacteroides activates IL-22 and reduces colitis. In the presence of LPS, Reg4 expressed in intestinal epithelial cells maintains immune homeostasis by increasing the proportion of Lactobacillus and its metabolite IAA, which promotes the production and accumulation of IL-35 + B regulatory (Breg) cells in intestinal tissues (71). IL-35-producing Breg cells are key immune regulators of many diseases, including autoimmune and infectious diseases and cancer progression (89).…”
Section: Indole Derivatives Enhance Immune Barriermentioning
confidence: 99%
“…It has been found that IPA acts as a ligand for PXR in vivo, and IPA downregulates enterocyte TNF-a while upregulating ligand-encoding mRNA and increasing the manifestation of TJs that regulate intestinal barrier function in terms of intestinal permeability and inflammation (74). IAA combined with the PXR receptor can cause the production of IL-35 + B cells, promoting potent antiinflammatory cytokine IL-35, which maintains intestinal homeostasis (71). In addition, indole and indole-3-acetamide have also been suggested as PXR agonists (110) (Table 2).…”
Section: Modulation Of Pregnancy-x Receptormentioning
confidence: 99%